Enhanced Skin Permeation of Punicalagin after Topical Application of Pluronic Micelles or Vesicles Loaded with Lafoensia pacari Extract - Garcia, Sandra Alves de Sousa; da Rocha, Priscila Bianca Rodrigues; Souza, Bruno dos Santos; Paz, Andressa Tuane Santana; Negris, Ana Luiza Caetano; Marreto, Ricardo Neves; da Conceição, Edemilson Cardoso; Bara, Maria Teresa Freitas; Taveira, Stephânia Fleury (Planta Medica, 2021)
Punicalagin, the principal ellagitannin of Lafoensia pacari leaves, has proven antioxidant activity, and standardized extracts of L. pacari can be topically used for skin aging management. We hypothesized that Pluronic nanomicelles or vesicles could solubilize sufficiently large amounts of the standardized extracts of L. pacari and provide chemical stability to punicalagin. The standardized extracts of L. pacari were obtained with an optimized extraction procedure, and the antioxidant activity was characterized. Formulations containing Pluronic at 25% and 35% were obtained with or without Span 80. They were characterized by average diameter, polydispersity index, punicalagin content, physicochemical stability, and rheology. A release and skin permeation study was carried out in vertical diffusion cells. The extraction procedure allowed quantifying high punicalagin content (i.e., 141.61 ± 3.87 mg/g). The standardized extracts of L. pacari showed antioxidant activity for all evaluated methods. Pluronic at 25 and Pluronic at 35 with standardized extracts of L. pacari showed an average diameter of about 25 nm. The addition of Span 80 significantly increased the mean diameter by 15-fold (p < 0.05), indicating the spontaneous formation of vesicles. Pluronic formulations significantly protected punicalagin from chemical degradation (p < 0.05). Pluronic at 25 formulations presented as free-flowing liquid-like systems, while Pluronic at 35 resulted in an increase of about 44-fold in |ƞ*|. The addition of Span 80 significantly reduced the Pluronic sol-gel transition temperature (p < 0.05), indicating the formation of vesicles. Formulations with Span 80 significantly enhanced punicalagin skin permeation compared to formulations without Span 80 (p < 0.05). Formulations with Span 80 were demonstrated to be the most promising formulations, as they allowed significant permeation of punicalagin (about 80 to 315 µg/cm2), which has been shown to have antioxidant activity.
Keywords: Lafoensia pacari; Lythraceae; antioxidant activity; supramolecular gels; topical administration; phytocosmetic